2015
DOI: 10.1534/genetics.115.179010
|View full text |Cite
|
Sign up to set email alerts
|

Genetical Genomics of Behavior: A Novel Chicken Genomic Model for Anxiety Behavior

Abstract: The identification of genetic variants responsible for behavioral variation is an enduring goal in biology, with wide-scale ramifications, ranging from medical research to evolutionary theory on personality syndromes. Here, we use for the first time a largescale genetical genomics analysis in the brains of chickens to identify genes affecting anxiety as measured by an open field test. We combine quantitative trait locus (QTL) analysis in 572 individuals and expression QTL (eQTL) analysis in 129 individuals fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(92 citation statements)
references
References 111 publications
(106 reference statements)
2
89
0
Order By: Relevance
“…Correlations between the two trials were found to be extremely significant (see supplementary figure 1), indicating that the tests were strongly repeatable. A high degree of correlation was found between the social reinstatement behaviour reported here, and the open field behaviour that was also recorded for these animals (and reported in (J OHNSSON et al 2016)), with 123 of the 224 pairwise correlation comparisons (these pairwise correlations were both within- and between-tests) being significant (using a 1% significance threshold, see supplementary figure 1).…”
Section: Methodssupporting
confidence: 77%
See 3 more Smart Citations
“…Correlations between the two trials were found to be extremely significant (see supplementary figure 1), indicating that the tests were strongly repeatable. A high degree of correlation was found between the social reinstatement behaviour reported here, and the open field behaviour that was also recorded for these animals (and reported in (J OHNSSON et al 2016)), with 123 of the 224 pairwise correlation comparisons (these pairwise correlations were both within- and between-tests) being significant (using a 1% significance threshold, see supplementary figure 1).…”
Section: Methodssupporting
confidence: 77%
“…in the F 8 . 129 of the 572 F 8 were used in an eQTL experiment, with the hypothalamus/thalamus dissected out at 212 days of age, RNA extracted and run individually on a 135k probe microarray (see (J OHNSSON et al 2016)). For further details on feed and housing see (J OHNSSON et al 2012b).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the genetic basis of predispositions for animacy cues and its individual variability, might have a crucial importance for translational studies on developmental pathologies, such as Autism Spectrum Disorders42. The use of chicks as system model is particularly suitable not only for the ease of handling and controlling precocial special species until the moment of test and for the established parallels between human newborns and chicks1, but also for the mounting evidence on the neurobiological basis of spontaneous predispositions7184344 and the availability of genomic tools45464748 and controlled populations with segregating variation1647.…”
Section: Resultsmentioning
confidence: 99%